Wages and gender composition : why do women's jobs pay less? - Macpherson, David A. [Verfasser]; Hirsch, Barry T. [Verfasser] (My University, 1995)
"Occupational sey segregation and its relationship with wages during 1973-93 are examined. Wage level and wage change models are estimated using Current Population Survey data matched with measures of occupational skills and job disamentities. Standard analysis confirms that wage levels are substantially lower in predominantly female occupation. Gender pomposition effects are reduced by about a quarter for women an by over one-half for men following control for skillrelated occupational characteristics. Longitudinal analysis indicates that two-third or more of the standard gender composition effect is accounted for by occupational characteristics and unmeasured worker skill or taste differences." (author's abstract, IAB-Doku) ((en)) Die Autoren untersuchen die Lohnentwicklung in den USA 1973-1993 nach Berufen. Je höher der Frauenanteil in einem Beruf, desto niedriger ist das Lohnniveau, auch für die männlichen Beschäftigten. Die Ursachen dafür werden regressionsanalytisch untersucht. (IAB)
Keywords: S 6 Berufsbereiche; G 2.4.5 Gender Mainstreaming; G 1.2.2.1 Lohn- & Tarifsysteme; G 1.2.3.1 Potenziale; I 2.3.2 Nordamerika; Frauenberuf; Männerberuf; Berufsgruppe; Geschlechterverteilung; Lohnhöhe; Einflussfaktor; Qualifikationsniveau; Quantitative Angaben; USA; 1973-1993